Deslocamentos cotidianos no espaço metropolitano: as trajetórias Maracanaú-Fortaleza - Sousa Neto, Francisco Oliveira de (2010)
At present, at the same time where if it deepen the social and territorial division of the work, the urban dynamics each time more combine, increase the speeds of the flows of matter (merchandises, people) and energy (information) that pervade the territories metropolitans. Multiples are the social subjects and agents (State, Capital) involved in these processes. Thus, mobility is a necessary condition the life in the cities. Indeed, this study aims to examine the context in which context happens the daily displacements, that occur in the Region Metropolitan of Fortaleza, from the integration of the cities of Maracanaú-Fortaleza. It is means of the daily displacements that highlight the social status of the resident, power relations and conflicts, that pervade the production of the metropolitan urban space. In synthesis, sought understand the limits and the strategical possibilities that mobility brings to the inhabitant in its right to the city, a life, a sociability, in order to beyond the production and of the consumption. Motivated by the search for work or other daily needs, this phenomenon if materializes as a class condition, where these subject redefine everyday life your conception of space, time and social rights.